Halberdiers and Combat Systems in the Argaric. Issue 4 (2nd October 2017) - Lull, Vicente; Micó, Rafael; Rihuete Herrada, Cristina; Risch, Roberto; Escanilla, Nicolau
Summary: The Argaric halberd is a specialized weapon for hand‐to‐hand combat, with its full development in the south‐east of the Iberian Peninsula between 2000 and 1800 cal BCE. This paper deals with the Argaric combat system and the factors that drove this type of confrontation, given the social order, the active and passive archaeological traces present in these weapons and their effects on the human body. This pragmatic order of directing interpersonal violence had three patriarchal socio‐political implications: the domestication of the body through the discipline of instruction and combat, a ritual of identification represented in funerary practices and a symbol of power, but only available to a small number of men. The Argaric halberdiers occupy an intermediate position in the transition between an armed man and a soldier, probably intersecting with the figures of the hero and the warrior. In Supporting Information Annexe 1, we develop a morphological description, based on the system of hafting the Argaric halberds and, in Annexe 2, we present the funerary contexts with interesting data for the combat system.